Análisis jurídico y comparado sobre la vulneración de Derechos Humanos a las personas que viven en la calle - Andrade Andrade, Rosa Angelica (2023)
The main objective of this Research Work is to study the violation of Human Rights of individuals living on the streets, from a Comparative Law perspective, while also advocating for the creation of a national legal framework in Ecuador to protect those who are living on the streets. The aim is to promote public policies and strategies to reduce poverty levels, foster economic growth, and enhance human and social development, ultimately addressing the dire reality faced by individuals living on the streets. This endeavor takes into account the current situation of the country, with a particular focus on generating employment opportunities to combat poverty, as well as improving public services, notably healthcare. Thus, this Research Work focuses on the study of Human Rights violations suffered by homeless people. It conducts a comparative legal analysis among different countries to identify public policies and legal measures implemented to safeguard these individuals. This academic study underscores the significance of recognizing individuals in street situations as rights holders rather than social burdens. It tackles the issue from a multidisciplinary perspective, encompassing social, economic, and cultural aspects. As conclusion, the necessity of implementing comprehensive public policies addressing the structural causes of street situations stands out, along with specific measures to ensure access to basic services like housing, healthcare, and education. Emphasis is also placed on respecting the human rights and dignity of these individuals, as well as raising societal awareness about this issue. The situation of individuals living on the streets is a global problem affecting millions worldwide. These individuals often confront numerous challenges, including lack of housing, food, medical care, and basic services. Moreover, they frequently are victims to discrimination and violence, enduring routine violations of their human rights. To address this issue, analyzing existing laws and policies in various countries and assessing their effectiveness in protecting the rights of individuals living on the streets is crucial. This may involve evaluating housing policies, social assistance programs, employment and training initiatives, as well as measures to combat discrimination and violence. 5 Governments, non-governmental organizations, and society at large must collaborate to tackle this issue and ensure the human rights of all individuals, including those who are living on the streets, are upheld. This could entail implementing new policies and programs, as well as revising and enhancing existing ones to ensure they are effective and equitable. Emphasis will be placed on the fact that poverty reduction is a fundamental responsibility of the Government, involving all its components, thereby necessitating joint and widespread actions involving the public and private sectors, as well as the individuals in street situations themselves. Methodologies such as interviews, surveys, and various analytical, deductive, inductive, scientific, and exegetical methods will facilitate a comprehensive analysis of all pertinent information.